Horatio Happened - Cave, Kathryn and Riddell, Chris (Hodder Headline Plc, 1998)
Jack hates tidying up and shoves everything under the bed. It fizzles and sizzles and Horatio is created. But what happens to Horatio when Jack's mother discovers the mess? From the award-winning team of Something Else!
Keywords: Juvenile literature-Fiction